Methylmercury uptake by diverse marine phytoplankton - Lee, Cheng-Shiuan; Fisher, Nicholas S. (Limnology and oceanography, 2016)
Phytoplankton may serve as a key entry for methylmercury (MeHg) into aquatic food webs however very few studies have quantified the bioconcentration of MeHg in marine phytoplankton from seawater, particularly for non-diatoms. Experiments using 203Hg to measure MeHg uptake rates and concentration factors in six marine phytoplankton species belonging to different algal classes were conducted and the influence of light, temperature, and nutrient conditions on MeHg bioaccumulation were determined. All algal species greatly concentrated MeHg out of seawater, with volume concentration factors (VCFs) ranging from 0.2 × 10⁵ to 6.4 × 10⁶. VCFs were directly related to cellular surface area-to-volume ratios. Most of the cellular MeHg was found in the cytoplasm. Temperature, light, and nutrient additions did not directly affect MeHg uptake in most species, with the exception that the dinoflagellate Prorocentrum minimum displayed significantly greater uptake per cell at 18°C than at 4°C, suggesting an active uptake for this species. Passive transport seemed to be the major pathway for most phytoplankton to acquire MeHg and was related to the surface area-to-volume ratio of algal cells. Environmental conditions that promoted cell growth resulted in more total MeHg associated with cells, but with lower concentrations per unit biomass due to biodilution. The very high bioconcentration of MeHg in marine phytoplankton is by far the largest bioconcentration step in marine food chains and variations in algal uptake may account for differences in the amount of MeHg that ultimately builds up in different marine ecosystems.